4 x (-3) = (-12)-12 +9 = (-3)so the answer is -3
2.8 times 4 plus 9 plus 3 minus 2.8 plus 4.2 is equal to 24.6
356,433,300
5 + 4 * 7 * 4 - 9 + 3 / 3 = 5 + 28*4 - 9 + 1 = 5 + 112 - 9 + 1 = 109
9 + 9 + 9 + 9 + 9 + 9 + 6 + 6 + 6 + 6 + 2 + 2 + 23 + 3 + 3 + 4 + 4 + 4 = 123
9 plus 16=25 3 squared is the same as 3 times three and 4 squared is the same as 4 times 4 3 times 3 + 4 times 4 9 plus 16 = 25
4 x (-3) = (-12)-12 +9 = (-3)so the answer is -3
3 times 4 times 9 plus 4 minus (3 times 4)
2.8 times 4 plus 9 plus 3 minus 2.8 plus 4.2 is equal to 24.6
356,433,300
5 + 4 * 7 * 4 - 9 + 3 / 3 = 5 + 28*4 - 9 + 1 = 5 + 112 - 9 + 1 = 109
9 + 9 + 9 + 9 + 9 + 9 + 6 + 6 + 6 + 6 + 2 + 2 + 23 + 3 + 3 + 4 + 4 + 4 = 123
12 divided by 4 plus 2 times 3 = 9
4 * (-4) + 9 = -7; so -7 is equivalent to 4 times -4 plus 9.
9
it doesn't
3 + 3 + 4 + 546 + 6767676767 + 9 = 6767677332